Inherited metabolic diseases are a potent risk factor for cytomegalovirus infection in pediatric living donor liver transplantation - Kentaro Ushijima; Yukihiro Sanada; Shinya Otomo; Keiko Ogaki; Taiichi Wakiya; Noriki Okada; Yuta Hirata; Toshio Horiuchi; Takahiko Omameuda; Kiichiro Takadra; Ryosuke Akimoto; Yasuharu Onishi; et al. (BMC Infectious Diseases)
Abstract Background Cytomegalovirus (CMV) is a major infectious complication in solid-organ transplant recipients, particularly in the context of pediatric liver transplantation. CMV serostatus is a well-established risk factor for postoperative CMV infection, with CMV seronegative recipients who receive organs from seropositive donors (D+/R−) being at the highest risk. Our previous research indicated a higher incidence of CMV infection in recipients with inherited metabolic diseases (IMDs) compared with those with biliary atresia (BA). This study aimed to determine whether IMDs constitute an independent risk factor for postoperative CMV infection. Methods We retrospectively analyzed data from 45 IMD and 230 BA recipients. We collected information on the occurrence and timing of episodes of CMV infections, methylprednisolone (mPSL) pulse therapy, patient characteristics, and peri- and postoperative data. Results Multivariable analysis identified mPSL pulse therapy (Odds Ratio (OR): 4.43), CMV serostatus (D+/R−) (OR: 6.03), and underlying IMDs (OR: 3.28) as independent risk factors for CMV infection. Further stratified analysis, which considered the timing of CMV infection diagnosis relative to mPSL pulse therapy, confirmed that CMV serostatus with (D+/R−) (OR: 5.61) and underlying IMDs (OR: 2.83) remained independent predictors of CMV infection, even when excluding the influence of mPSL pulse therapy. Conclusions This study demonstrates that IMDs are a potent independent risk factor for CMV infection following pediatric liver transplantation. Clinical trial number Not applicable.